Tackling Poverty in Era of Covid-19 Pandemic: The Contributory Pension Option (2021)
In December 2019, news broke out that a novel coronavirus has hit the city of Wuhan, China. It was reported that the SARS-CoV2 virus is responsible for the Covid-19 pandemic. The coronavirus pandemic has impacted severely on the country. As expected, the pandemic has worsened the fate of the poor and most vulnerable households in Nigeria. To cushion the impact, the federal government of Nigeria (FGN) has instituted various palliative measures including cash grants of N5,000 (US$14) monthly to approximately 1 million vulnerable households. However, a review of these measures shows that they are grossly inadequate and incapable of any meaningful impact on the suffering of the masses. The government is clearly hamstrung in this regard due to huge shortfalls in revenue as a result of the pandemic. To this end, the study reviewed the contributory pension scheme in Nigeria and recommended that government should leverage on the pension fund which is currently in excess of ₦7 trillion. The study argued that government should amend the extant regulatory framework for recovery of pension contribution to enable the contributors to access up to 30% of their contributions to help cushion the effect of the coronavirus pandemic. These withdrawals will be restored through increased accretion to the funds by government and private sector employers when normalcy returns to the country. This will help to alleviate the sufferings of over 9 million Nigerians who are currently enrolled on the pension scheme.